Posibilidades de innovación social para comunidades de pequeños comerciantes de productos agricolas (Revista cientifica In Vestigium Ire, 2016)
The main asset is a community to engage in the transformation process, successful integration is to unite efforts of different actors in society, creating value as protagonists of their own development. The aim of this paper is to analyze from different theoretical framework of social innovation practices from the conditions of a group of small traders of agricultural products. The methodology of this study is qualitative descriptive, interviews and focus group are used. The results show the need for coordination and to build consensus on projects that generate social value from reading the local reality, because it shows that despite being a vulnerable population, there are various ways they can improve from economic and social.
Keywords: Social innovation; agricultural products; local development; informal organizations